2021
DOI: 10.1002/adma.202107643
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Control in 3D Printed Materials

Abstract: Currently, there are no straightforward methods to 3D print materials with nanoscale control over morphological and functional properties. Here, a novel approach for the fabrication of materials with controlled nanoscale morphologies using a rapid and commercially available Digital Light Processing 3D printing technique is demonstrated. This process exploits reversible deactivation radical polymerization to control the in‐situ‐polymerization‐induced microphase separation of 3D printing resins, which provides m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 59 publications
6
75
0
Order By: Relevance
“…Upon increasing the macroCTA wt % from 16.5 to 43.9 wt % for the R2‐180 resins, the q* value of the SAXS profiles increased from 0.28 nm −1 to 0.33 nm −1 (Figure 6C), revealing a slight decrease in the domain spacing ( d SAXS ) from 22 nm to 19 nm. The decrease in d SAXS is consistent with our previous study using linear (1‐arm) macroCTA, which was ascribed to reduction in average block copolymer size upon higher loading of macroCTA in a resin [24] . Similarly, SAXS profiles of materials 3D printed using R4‐180 resins also displayed the same trend, with d SAXS decreasing from 16 nm to 13 nm upon increasing macroCTA wt % from 16.5 to 43.9 wt % (SI, Figure S12).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Upon increasing the macroCTA wt % from 16.5 to 43.9 wt % for the R2‐180 resins, the q* value of the SAXS profiles increased from 0.28 nm −1 to 0.33 nm −1 (Figure 6C), revealing a slight decrease in the domain spacing ( d SAXS ) from 22 nm to 19 nm. The decrease in d SAXS is consistent with our previous study using linear (1‐arm) macroCTA, which was ascribed to reduction in average block copolymer size upon higher loading of macroCTA in a resin [24] . Similarly, SAXS profiles of materials 3D printed using R4‐180 resins also displayed the same trend, with d SAXS decreasing from 16 nm to 13 nm upon increasing macroCTA wt % from 16.5 to 43.9 wt % (SI, Figure S12).…”
Section: Resultssupporting
confidence: 91%
“…AFM measurements in PeakForce quantitative nanomechanics mode was used to investigate the nanostructure of 3D printed materials. It has been reported that soft PBA and hard PAA domains on 3D printed material surfaces can be distinguished due to elastic modulus differences [24] . Detailed parameters applied in the AFM study can be found in the SI, Characterization section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, our group recently developed a photoinduced 3D printing process using polymerization induced microphase separation (PIMS), to fabricate materials with nanostructured domains 21 . The PIMS process was originally developed by Seo and Hillmyer 22 , and relies on in-situ chain extension of a macromolecular chain transfer agent (macroCTA) to induce microphase separation between incompatible block segments; the microphase separation is then arrested via crosslinking which provides materials with nanoscale morphologies (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[63] Furthermore, Boyer group demonstrated that RAFT 3D printing can be used for silica/polymer composite fabrication (Figure 5E) [64] as well as micro-to nanoscale structure control in 3D printed complex objects. [65] Recently, Jin and co-workers explored the possibility of RAFT 3D printing under red LED light (635 nm, 0.5 mW cm −2 ) by introducing ZnTPP to the resin, with a disk-shaped model printed. [66] Meanwhile, Zhu and co-workers attempted cationic RAFT polymerization toward NIR light 3D printing by using a commercially available iron catalyst, cyclopentadienyl iron dicarbonyl dimer (Fe 2 (Cp) 2 (CO) 4 ) as the photocatalyst.…”
Section: Raft Photoinitiating Systemmentioning
confidence: 99%